Altered neuromagnetic activity under visual stimuli in migraine: a multi-frequency magnetoencephalography study - Di Wu; Zhiyuan Zhou; Yingfan Wang; Hongxing Liu; Yuanwen Yu; Qiqi Chen; Xiaoshan Wang (Frontiers in Neurology, 2025)
BackgroundMigraine is a chronic neurological disorder associated with a variety of abnormal visual symptoms. However, the mechanisms of visual processing in migraine are not fully understood. This study aimed to investigate neuromagnetic activity abnormalities under visual stimuli in migraine patients using magnetoencephalography (MEG).MethodsMagnetoencephalography recordings during exposure to visual stimuli were collected for 22 episodic migraine patients without aura during the interictal period and 22 age- and gender-matched healthy controls (HCs). The spectral power and functional connectivity (FC) of visual neuromagnetic activation were estimated using minimum norm estimation combined with the Welch technique and corrected amplitude envelope correlation.ResultsCompared to HCs, migraineurs exhibited attenuated spectral power in the gamma2 band of the bilateral medial orbitofrontal cortices, bilateral posterior cingulate cortices, bilateral temporal poles, right lateral orbitofrontal cortex, and left transverse temporal cortex. Migraineurs also exhibited the following increases in FC relative to HCs between vision- and pain-related brain regions: In the alpha band, FC between the left cuneus and left medial orbitofrontal cortex was significantly increased. In the beta band, FC between the left lateral occipital cortex and bilateral anterior cingulate cortices was significantly increased. In the gamma1 band, FC of the right cuneus with the bilateral insulae, left parahippocampal cortex, bilateral posterior central cortices, and bilateral anterior cingulate cortices was significantly increased. Migraineurs also showed significantly increased FC between the left lateral occipital cortex and the right medial orbitofrontal cortex, left posterior central cortex, and bilateral anterior cingulate cortices. The clinical variables (headache history, attack frequency, and pain intensity) had no significant correlation with MEG results.ConclusionTaken together, these findings demonstrate altered spectral power in pain-processing regions and altered FC between vision and pain-related regions in migraineurs under visual stimuli in multi-frequencies. These results may contribute to understanding the relationship between visual dysfunction and headache onset in migraineurs, providing valuable insights into the underlying pathophysiology.